Between Stories and Struggles: A Narrative Inquiry and Micro-Political Study of Undergraduate Thesis Supervision - Thabran, Yulhenli (Ethical Lingua: Journal of Language Teaching and Literature, 2026)
This study examines English lecturers’ experiences of supervising undergraduate theses in an Indonesian university, focusing on how supervisory practices are shaped by lived experience and institutional power relations. Drawing on a synthesized framework integrating narrative inquiry and micro-political theory, supervision is conceptualized as both a narratively constructed practice and a politically negotiated process. Employing a qualitative research design, in-depth interviews were conducted with 11 English lecturers of varying seniority. The data were analyzed iteratively through within-case and cross-case thematic analysis guided by the three-dimensional inquiry space of narrative inquiry and Ball’s micro-political concepts of power, interests, and negotiated order. The findings demonstrate that supervisory authority is exercised through informal negotiation within an incoherent institutional structure, that students’ difficulties are largely institutionally produced rather than individually caused, that both students and junior supervisors experience micro-political vulnerability, and that emotional labor operates as a compensatory mechanism sustaining supervisory practice. Overall, the study shows that undergraduate thesis supervision functions not as a purely procedural task but as an emotionally sustained and micro-politically negotiated practice, underscoring the need for clearer institutional support and greater attention to power relations in undergraduate thesis supervision. Keywords: thesis supervision; lecturer experience; supervisory practices; institutional context; higher education